THE EFFECT OF IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE, COMPANY SIZE, AND FREE CASH FLOW ON EARNINGS MANAGEMENT - Fitriyana, Fina (Universitas Sam Ratulangi, 2020)
The aims of this study is to examine the effect of the good corporate governance, company size, and free cash flow on the earnings management for companies in food and beverage sector at Indonesia Stock Exchange in period of 2012 until 2016. This study conducts regression analysis in term of hypothesis testing. This study finds that board of directors and board of commissioners are significant on earnings management, while the commissioners and audit committee, firm size and free cash flow are insignificant.